Future Mangrove Carbon Storage Under Climate Change and Deforestation - Chatting, Mark; Al-Maslamani, Ibrahim; Walton, Mark; Skov, Martin W.; Kennedy, Hilary; Husrevoglu, Y. Sinan; Le Vay, Lewis (Frontiers in Marine Science, 2022)
Mangroves are important sinks of organic carbon (C) and there is significant interest in their use for greenhouse gas emissions mitigation. Adverse impacts on carbon storage potential from future climate change and deforestation would devalue such ambitions, thus global projections of future change remains a priority research area. We modelled the effects of climate change on future C stocks and soil sequestration rates (CSR) under two climate scenarios (‘business as usual’: SSP245 and high-emissions: SSP585). Model results were contrasted with CO2 equivalents (CO2e) emissions from past, present and future rates of deforestation on a country specific scale. For C stocks, we found climate change will increase global stocks by ~7% under both climate scenarios and that this gain will exceed losses from deforestation by the end of the 21st century, largely due to shifts in rainfall. Major mangrove-holding countries Indonesia, Malaysia, Cuba and Nigeria will increase national C stocks by >10%. Under the high-end scenario, while a net global increase is still expected, elevated temperatures and wider temperature ranges are likely increase the risk of countries’ C stocks diminishing. For CSR, there will likely be a global reduction under both climate change scenarios: 12 of the top 20 mangrove-rich countries will see a drop in CSR. Modelling of published country level mangrove deforestation rates showed emissions have decreased from 141.4% to 6.4% of annual CSR since the 1980’s. Projecting current mangrove deforestation rates into the future resulted in a total of 678.50 ±151.32 Tg CO2e emitted from 2012 to 2095. Reducing mangrove deforestation rates further would elevate the carbon benefit from climate change by 55-61%, to make the proposition of offsetting emissions through mangrove protection and restoration more attractive. These results demonstrate the positive benefits of mangrove conservation on national carbon budgets, and we identify the nations where incorporating mangrove conservation into their Nationally Defined Contributions offers a particularly rewarding route towards meeting their Glasgow Agreement commitments.